2015
DOI: 10.1088/0004-637x/800/1/42
|View full text |Cite
|
Sign up to set email alerts
|

The Maunder Minimum Is Not as Grand as It Seemed to Be

Abstract: The Maunder Minimum (MM), which occurred between 1645 and 1715, is mainly known as an almost spotless period on the Sun. We analyze the nominal number of sunspot groups for each observer individually. Comparing the sunspot drawings and textual reports, we conclude that the latter underestimate the number of sunspots. We also argue that the different points of view of observers in the seventeenth century on the origin of sunspots resulted in the underestimation of sunspot groups or even gaps in observational re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
69
6
2

Year Published

2015
2015
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(85 citation statements)
references
References 28 publications
(49 reference statements)
7
69
6
2
Order By: Relevance
“…1705. Even this very strict model suggests that the cycles were lower than 15-20 in sunspot numbers, which is much lower than the present cycle #24 and an order of magnitude lower than the very high cycles proposed by Zolotova & Ponyavin (2015). Considering the severe reduction of the statistics and a possible strong bias towards active days in the MS model, we believe it is not indicative of the true solar activity evolution during the MM and may represent only the uppermost upper (maximum maximorum) bound.…”
Section: Sunspot Numberscontrasting
confidence: 74%
See 1 more Smart Citation
“…1705. Even this very strict model suggests that the cycles were lower than 15-20 in sunspot numbers, which is much lower than the present cycle #24 and an order of magnitude lower than the very high cycles proposed by Zolotova & Ponyavin (2015). Considering the severe reduction of the statistics and a possible strong bias towards active days in the MS model, we believe it is not indicative of the true solar activity evolution during the MM and may represent only the uppermost upper (maximum maximorum) bound.…”
Section: Sunspot Numberscontrasting
confidence: 74%
“…Nevertheless, Hoyt & Schatten (1998a) adopted solar observations recorded in this source as no-spot reports, which is not correct. It has been discussed that, while the definition of sunspot numbers and even sunspot groups is not very reliable in the earlier part of the GSN Article published by EDP Sciences A71, page 1 of 6 series (Clette et al 2014;Zolotova & Ponyavin 2015), solar activity during the MM can be reliably represented by the fraction of active days (Kovaltsov et al 2004;Vaquero et al 2012Usoskin 2013). Despite the overall level of activity, the parameters of the solar cyclic variability during MM are also important to know.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, sunspots appeared rarely (during ∼2% of the days) and seemingly sporadically, without an indication of the 11-year cycle. Some recent studies suggested that the sunspot activity level might have been underestimated during MM: Zolotova and Ponyavin (2015) proposed that the annual number of sunspot groups was as high as 3-8 (the sunspot number 50-100) during MM, Svalgaard and Schatten (2016) proposed much more modest peak annual number of sunspot groups as 2-3 (25 -40 in sunspot number) but still too high. These claims were based on the fact that original data include many generic statements of the absence of sunspots for long periods of time, and should be dismissed.…”
Section: The Maunder Minimummentioning
confidence: 99%
“…Some of these suggestions were based on a mathematical synthesis using empirical rules in a way similar to Schove (1955) and Nagovitsyn (1997) and therefore are not true reconstructions. Some others used a re-analysis of the direct A&A 581, A95 (2015) data series (Rek 2013;Zolotova & Ponyavin 2015) and provide claimed assessments of the solar variability. While earlier suggestions have been convincingly rebutted by Eddy (1983), the most recent ones are still circulating.…”
Section: Introductionmentioning
confidence: 99%